Pembuatan Website Kelompok Usaha Perhutanan Sosial (KUPS) Register Lima dan Pelatihan Pemanfaatannya dalam Mendukung Pemasaran Produk Kopi Agroforestry - Putra, Yusran Panca; Oktoyoki, Hefri; Faradik, Mela; Paulina, Maria (Universitas Pattimura, 2023)
Training on the use and creation of websites for Social Forestry Business Groups (KUPS) has the main objective of empowering KUPS members in managing and utilizing online platforms as effective marketing tools. With a focus on agroforestry coffee marketing, this training aims to increase visibility and market access for KUPS products. The methods used are: 1) Designing and creating the Website; 2) conducting training on website management and utilization for KUPS Register Lima members in Tebat Village, Pulau Rejang Lebong. The results of the community service show that this training has had a positive impact on members' marketing capabilities, supported local economic growth, and overall strengthened KUPS's contribution to the agroforestry sector.